SIRT1 Alleviates Mitochondrial Fission and Necroptosis in Cerebral Ischemia/Reperfusion Injury via SIRT1–RIP1 Signaling Pathway - Xuan Wei; Hanjing Guo; Guangshan Huang; Haoyue Luo; Lipeng Gong; Pan Meng; Jiyong Liu; Wenli Zhang; Zhigang Mei (MedComm)
ABSTRACT Programmed cell death, including necroptosis, plays a critical role in the pathogenesis of cerebral ischemia/reperfusion injury (CIRI). Silent information regulator 1 (SIRT1) has been identified as a potential therapeutic target for CIRI, yet its precise role in regulating necroptosis remains controversial. Furthermore, the potential interaction between SIRT1 and receptor‐interacting protein kinase 1 (RIP1) in this context is not fully understood. Sanpian Decoction (SPD), a classical traditional herbal formula, was previously shown to enhance SIRT1 expression in our studies. Our findings demonstrated that, both in vivo and in vitro, CIRI was associated with a decrease in SIRT1 levels and phosphorylated dynamin‐related protein 1 (p‐DRP1) at Ser637, alongside an increase in RIP1 and other necroptosis‐related proteins. Co‐immunoprecipitation and immunofluorescence analyses revealed a weakened interaction between SIRT1 and RIP1. Furthermore, abnormal mitochondrial fission and dysfunction were mediated through the phosphoglycerate mutase 5–DRP1 pathway. Notably, SPD treatment improved neurological outcomes and reversed these pathological changes by enhancing the SIRT1–RIP1 interaction. In conclusion, this study suggests that SIRT1 is a promising therapeutic target for CIRI, capable of inhibiting necroptosis and mitigating mitochondrial fission via the SIRT1–RIP1 pathway. SPD exhibits therapeutic potential by activating SIRT1, thereby attenuating necroptosis and mitochondrial fission during CIRI.